2015
DOI: 10.1590/0001-3765201520140166
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of nutritional composition and potential use of some underutilized tropical fruits of Arecaceae

Abstract: In this study, pulp and kernel of fruits from six Arecaceae species were subjected to proximate analysis, fatty acid composition and total carotenoid content analysis. The species with the highest carbohydrate, lipid and protein values were Ptychosperma macarthurii (70.1 g/100 g in the kernel), Syagrus cearensis (40.6 g/100 g in the kernel), and S. coronata (20.6 g/100 g in the pulp). The ash content ranged from 0.61 to 7.51 g/100 g. Lauric, palmitic, and oleic acids were the major fatty acids identified. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
3
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 20 publications
6
32
3
8
Order By: Relevance
“…In the present study, the chemical composition of whole carnauba fruit, and its pulp and kernel were independently assessed, as shown in Table 3. Silva et al (2015b) evaluated several fruit species belonging to the Arecaceae family, and observed that for most species, the total protein contents of the pulp (1.50 to 20.60 g 100 g -1 ) and kernel (2.60 to 11.70 g 100 g -1 ) resented a wide variation, but was typically higher in the kernel relative to the pulp. One exception was Syagrus cearensis, which had the highest content in the pulp as seen in kernel (20.60 g 100 g -1 versus 4.30 g 100 g -1 ) (Silva et al, 2015b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the chemical composition of whole carnauba fruit, and its pulp and kernel were independently assessed, as shown in Table 3. Silva et al (2015b) evaluated several fruit species belonging to the Arecaceae family, and observed that for most species, the total protein contents of the pulp (1.50 to 20.60 g 100 g -1 ) and kernel (2.60 to 11.70 g 100 g -1 ) resented a wide variation, but was typically higher in the kernel relative to the pulp. One exception was Syagrus cearensis, which had the highest content in the pulp as seen in kernel (20.60 g 100 g -1 versus 4.30 g 100 g -1 ) (Silva et al, 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al (2015b) evaluated several fruit species belonging to the Arecaceae family, and observed that for most species, the total protein contents of the pulp (1.50 to 20.60 g 100 g -1 ) and kernel (2.60 to 11.70 g 100 g -1 ) resented a wide variation, but was typically higher in the kernel relative to the pulp. One exception was Syagrus cearensis, which had the highest content in the pulp as seen in kernel (20.60 g 100 g -1 versus 4.30 g 100 g -1 ) (Silva et al, 2015b). Braga (1960) reported that values of protein relatively close to those obtained in the present study for the pulp content (5.46%) and higher values for the kernel (6.89%), compared to those found in present study (6.30, 5.21 and 4.50% in the dried whole fruit, the pulp and fresh kernel, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…O teor de umidade de amêndoas é variável em função da espécie, beneficiamento de frutos e técnica de extração. Silva et al (2015) encontraram os seguintes níveis de umidade em amêndoas de arecáceas: Acrocomia intumescens -macaúba (62,2%), Pinanga kuhlii -pinanga (22,9%), Ptychosperma macarthurii -palmeira de macarthurii (65,4%), Syagrus cearensiscoco babão (72,5%), Syagrus coronata -licuri (74,9%) e Veitchia merrillipalmeira de manila (74,4%). Os autores coletaram os frutos e ocorreu armazenamento a 4°C até a execução das análises.…”
Section: Resultsunclassified
“…Este teor é muito superior a espécies oleaginosas usadas na fabricação de óleos comerciais, tais como: soja (18-20%), algodão (21%), canola (24-27%), amendoim (41,3%) (Constantino et al, 2014;Silva et al, 2015), porém inferior a amendoim (44,57%), avelã (63,18%), baru (41,04%), castanhade-caju (42,06%), castanha-do-Brasil (64,94%), macadâmia (66,16%), noz (65,07%), pecã (62,14%) e pistache (45,83%) (FREITAS & VELOSO, 2010).…”
Section: Resultsunclassified
See 1 more Smart Citation